Advancements in Hydrogel-Based Drug Sustained Release Systems for Bone Tissue Engineering - Zhang, Yunfan; Yu, Tingting; Peng, Liying; Sun, Qiannan; Wei, Yan; Han, Bing (Frontiers in Pharmacology, 2020)
Bone defects caused by injury, disease or congenital deformity remain a major health concern, and efficiently regenerating bone is a prominent clinical demand worldwide. However, bone regeneration is an intricate process that requires concerted participation of both cells and bioactive factors (BFs). Mimicking physiological bone healing procedures, the sustained release of bioactive molecules plays a vital role in creating an optimal osteogenic microenvironment and achieving promising bone repair outcomes. The utilization of biomaterial scaffolds can positively affect the osteogenesis process by integrating cells with BFs in a proper way. A high water content, tunable physio-mechanical properties and diverse synthetic strategies make hydrogels ideal cell carriers and controlled drug release reservoirs. Herein, we reviewed the current advancements in hydrogel-based drug sustained release systems that have delivered osteogenesis-inducing peptides, nucleic acids, and other bioactive molecules in bone tissue engineering (BTE).